Penerapan Hukum Cambuk dalam Perspektif Pendidikan Islam - Qurrotul Ainiyah (Proceedings of Annual Conference for Muslim Scholars, 2018)
Caning Law in Islam is given to adulterers, accusers of adultery and drunks orkhamr drinkers (intoxicating drinks) with the aim is to provide a deterrent effect, regret that will not be repeated again. As Indonesia is not an Islamic state, this law considered as not a positive law and can not be generallyapplied. However, with certain considerations and purposes, this law is applied at Pondok Pesantren al-Urwatul Wutsqo Jombang. This is a qualitative study using interviews, documentation and observation methods to discuss the other side of the caning law application at Pondok Pesantren Al- Urwatul Wutsqo Jombang with the concept of Islamic education as analytical methods. This study resulted that santri who had been punished by whips were Zina and Khamrdrunkers. They asked to be punished for their own consciousness and request as a process of repentance. The practice of wirid, taubat prayer and fasting are done before the punishment. Awareness of this repentance also as a result of educational processwhich applied in the pesantren.